A rapid method for the assessment of the vitality of microorganisms using flow cytometry. Issue 7 (8th April 2022) - Bouix, Marielle; Ghorbal, Sarrah; Picque, Daniel; Perret, Bruno; Saulou‐Bérion, Claire
Abstract: Cultivability, viability, and vitality make it possible to characterize the behavior of a cellular population. Vitality was assessed using the kinetic parameters of specific metabolisms depending on whether the strains were used, for example, for the acidification of lactic acid bacteria or for CO2 production in fermenting yeasts. However, these methods are time‐consuming. We developed a cytometric descriptor based on the energy‐dependent extrusion of carboxyfluorescein from cells, subsequent to carboxyfluorescein diacetate staining, and compared it to the measurements of metabolic activities of various bacteria and yeasts. For all of the microorganisms tested, the cytometric descriptor ΔFI15 was well correlated with the results of the metabolic measurements and, moreover, has the advantage of being easier and faster to use than metabolic methods. It can be very useful for evaluating the vitality of the starters before inoculation in industrial processes.